Effectiveness of the Contextualized Workbook in Improving Learners’ Sentence Writing Skills - Jacky S. Quintanilla; Jelliane Mae F. Bagarinao; Darlyn Q. Maca; Diane Mae P. Ulanday-Lozano; Precy M. Regalado; Paul R. Olvis; Michael B. Cahapay (NAJAHA, 2026)
This study aimed to determine the effectiveness of a contextualized workbook in improving the sentence writing skills of Grade 5 learners at Pedro Acharon Sr. Central Elementary School, General Santos City, during the School Year 2025–2026. The study employed a single-group experimental research design involving forty (40) purposively selected Grade 5 learners identified as having difficulties in sentence writing. Data were gathered through pre-test and post-test assessments using the same writing prompt and analytic scoring rubric focusing on sentence construction, grammar accuracy, verb forms and tenses, modifiers and complements, coherence, and mechanics. The findings revealed that learners obtained a pre- test mean percentage score of 45.58, which was interpreted as “Did Not Meet Expectations.” After the implementation of the contextualized workbook, the learners’ mean percentage score increased to 69.33. Although the post-test performance remained below the 75% mastery level, the improvement indicates progress in learners’ sentence writing skills. A paired-samples t-test revealed a significant difference between the pre-test and post-test scores of the learners. The findings suggest that the contextualized workbook may serve as a useful supplementary instructional material in supporting the development of sentence writing skills among Grade 5 learners. Based on the findings, it is recommended that teachers consider integrating contextualized materials alongside other writing strategies to support learners’ writing development. Future researchers may conduct studies involving larger samples, longer intervention periods, and control groups to further determine the effectiveness of contextualized workbooks in improving writing skills.